Family screening in brugada syndrome patients. (14th October 2021) - Cardoso, A; Faria, B; Von Hafe, P; Dias, G; Pereira, T; Ribeiro, S; Calvo, L; Oliveira, M; Fernandes, M; Sanfins, V; Lourenco, A
Abstract: Background: Brugada syndrome (BS) is a rare inherited channelopathy associated with sudden cardiac death (SCD) and family screening (FS) of index patients (pts) is recommended. However, data about pts identified through FS is lacking. Aim: To compare index pts to non-index pts identified through systematic FS. Methods: Single-center retrospective study of BS pts followed by the Arrhythmology Department. FS was offered to 1st degree relatives of all index pts through primary care services and a once-weekly voluntary open appointment. Genetic counselling was performed when indicated. Index and non-index pts were compared regarding baseline characteristics and events during the follow-up (syncope of probable arrhythmic origin, ventricular tachycardia/ventricular fibrillation (VT/VF) and SCD). Results: We included 165 pts (61% males, mean age 47±15 years) and 72 (44%) were identified through FS. Non-index pts were diagnosed at a younger age (42±14 vs 51±14 years, p <.001), were more often female (57% vs 25%, p<.001), were diagnosed predominantly through provocative test with ajmaline/flecainide (88% vs 47%, p<.001) and had less documented spontaneous type 1 ECG pattern (17% vs 59%, p<.001). A type 2 pattern was identified in 18 (25%) non-index pts. Genetic testing was performed in 38 (53%) non-index pts: 6 had a pathogenic SCN5A mutation, 18 a likely pathogenic SCN5A mutation and 12 a mutation of uncertain significance. At diagnosis, 24 (33%) non-index pts had history of syncope, 3 (4%) had nocturnal agonal respiration and 11 (15%) had palpitations with no differences between both groups (p=.119). Non-index pts were less likely to implant a cardioverterdefibrillator (14% vs 38%, p=.001). During a median follow-up of 28 (IQR 16–41) months, 10 (6%) pts had an event - 2 (3%) in the non-index group (2 syncope) and 8 (9%) in the index group (1 syncope; 7 VT/VF) - with no significative differences between groups (p=.432). There were nocardiovascular deaths. Conclusions: FS identified a considerable proportion of BS pts. Non-index pts were younger at the time of the diagnosis and had less spontaneous type 1 pattern. No differences were found in events between index and non-index pts, however, the event rate was low. Systematic FS can identify individuals at risk of SCD earlier, allowing close monitoring and, when indicated, appropriate treatment. Funding Acknowledgement: Type of funding sources: None.